Considering the role of behaviors in sustainability and climate change education - Eilam, Efrat (Frontiers in Psychology, 2025)
At the heart of sustainability and climate change education discourse is the notion of student behavioural change, as an emphasised goal. The central positioning of behaviour modification raises moral and ethical concerns, as well as concerns regarding the impacts on student well-being. In addressing these issues, this conceptual paper interrogates the role ascribed to student behaviour in sustainability education and climate change education.Multiple lenses are applied to critique the behavioural modification approach. Finally, it is proposed to reframe the role of behaviour and to conceptualise behaviour as forming part of ethics education, where the focus shifts from assigning behaviour an instrumental role to conceptualising its intrinsic educational value.